(untitled) (Global Journal of Management and Business Research, 2014)
Technological innovation not only enable a broader reach for consumer banking and financial services in Indian banking sector, but also enhances its capacity for continued and inclusive growth. E-developments in the arena of ATMs, debit cards, credit cards and mobile banking are changing the way businesses work. While customers get the convenience of 24×7 banking, the bank saves in heavy real estate and manpower costs when compared to establishing a branch. The results are indicative of technology invasion in banks as is obvious from increasing number of ATMs, debit and credit cards. But on the flip side the number of branches of foreign sector banks is still limited in rural and semi-urban areas. ANOVA results highlight that there is a significant difference in the number of branches and private, public and foreign sector banks. ANOVA results for ATMs also highlight that there is a significant difference in the ATMs of private, public and foreign sector banks.